A Meta-analysis of Antimicrobial Peptide Effects on Intestinal Bacteria, Immune Response, and Antioxidant Activity of Broilers - M. M. Sholikin; A. T. Wahyudi; A. Jayanegara; J. Nomura; Nahrowi Nahrowi (Faculty of Animal Science, Bogor Agricultural University, 2021)
This study used a meta-analysis to systematically assess the effect of antimicrobial peptide (AMP) addition on the number of bacteria, immune responses, and antioxidant activity of broilers. The database was compiled from 29 post evaluation articles that were found in search engines consisted of 36 experiments and 111 data. The mixed model method was used to assess the effect of AMP, with AMP addition level as a fixed effect and experiment as a random effect. The fixed effect was tested for linear and quadratic models. The quadratic model was retained when significant at p<0.05 but turned into its corresponding linear model when insignificant. In the starter phase, AMP addition decreased the number of bacteria in the ileum (coliform and total aerobic bacteria (TAB); (p<0.05), the caecum (Clostridium spp., Escherichia coli, coliform, and lactic acid bacteria (LAB); p<0.05), and excreta (Clostridium spp.; p<0.1). Similarly, the number of bacteria also declined in the ileum (Escherichia coli, p<0.05; TAB, p<0.1), the caecum (LAB; p<0.1), and excreta (Clostridium spp.; p<0.05) of broilers in the finisher phase. There were significant improvements in immune response and antioxidant activity in starter broiler, as indicated by the titer of Newcastle disease (ND) antibody, bursal index, spleen index, and thymus index (p<0.05) due to AMP addition. Variables of immunoglobulin M (IgM), cluster of differentiation 4 (CD4), ND antibody titer, bursal index, spleen index, and thymus index were also significantly increased (p<0.05) while superoxide dismutase activity (SOD activity) tended to increase (p<0.1) in finisher broiler following the AMP addition. In short, AMP addition is able to suppress the number of pathogenic bacteria and increase the immune response and antioxidant activity of broilers.